2021
DOI: 10.1101/2021.03.10.21253064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of anti-SARS-CoV-2 antibody testing in asymptomatic or mild COVID-19 patients in outbreak on a cruise ship

Abstract: Background A few studies on antibody testing have focused on asymptomatic or mild coronavirus disease 2019 (COVID-19) patients with low initial anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody responses. Anti-SARS-CoV-2 antibody-testing performance was evaluated using blood samples from asymptomatic or mild COVID-19 patients. Methods Blood samples were collected from 143 COVID-19 patients during an outbreak on a cruise ship 3 weeks after diagnosis. Simultaneously, a second SARS-CoV-2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…[19] Moreover, suspected re-infection was reported afterward by two participants in spite of seropositivity. This accorded well with previous studies that reported lower antibody levels among asymptomatic/pauci-symptomatic individuals than in severe COVID-19 patients, [1,4,8,9,13,17,20,21] probably owing to exposure to a number of viral particles below the infectious dose. [9] However, inducing anti-SARS-CoV-2 neutralizing antibody production upon re-infection in one asymptomatic patient has already been reported.…”
Section: Discussionsupporting
confidence: 92%
“…[19] Moreover, suspected re-infection was reported afterward by two participants in spite of seropositivity. This accorded well with previous studies that reported lower antibody levels among asymptomatic/pauci-symptomatic individuals than in severe COVID-19 patients, [1,4,8,9,13,17,20,21] probably owing to exposure to a number of viral particles below the infectious dose. [9] However, inducing anti-SARS-CoV-2 neutralizing antibody production upon re-infection in one asymptomatic patient has already been reported.…”
Section: Discussionsupporting
confidence: 92%